FIRE SAFETY DESIGN OF A 5 STOREY OFFICE BUILDING: EARLY WARNING AND MEANS OF ESCAPE (FUDMA JOURNAL OF SCIENCES, 2023)
A fire safety design on the early warning and means of escape for a 5 storey, Asha Office Building is conducted. This is to attain realistic standards of health and safety for persons within and outside the building. Manual alarm system (type M) along with L1 smoke detector were considered. L4 smoke detectors were to be fixed in the corridors and escape routes so as to provide an early warning of fires and smokes. The kitchen is to be covered with a heat detector. Simultaneous evacuation strategy with the capacity to allow all floors to be evacuated at the same time was considered on this design building. This was based on a total floor size of 15,275 m2 and 1,038 occupants with only one main entrance. This necessitated for alternative exits to be provided in order for all the people to evacuate on time, limit the travel distances and also to make the occupants have options to other exits should in case the main entrance is blocked with fire. The building occupants from the farthest distance on the ground floor would be expected to evacuate the building within 4 minutes. Also, by providing a safety margin, a tenability condition in the building would be maintained for a minimum of 8 minutes. For emergency lightings that would aid escape of occupants, five, four and two luminaires would be required to be arranged axially and spaced 4.8 m apart for the vertical, horizontal and dead-end corridors respectively.
Keywords: Fire safety; early warning; means of escape; office building